New Approaches to the Book Alpha Meizon of Aristotle’s Metaphysics and to its Unique Neoplatonic Commentary by Asclepius of Tralles - Wesoły, Marian (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2013)
review: R. Loredana Cardullo (a cura di), Il libro Alpha della Metafisica di Aristotele tra storio - grafia e teoria , Catania 2009, pp. 294. R. Loredana Cardullo, A sclepio di Tralle. Commentario al libro Alpha Meizon ( A ) della Metafisica di Aristotele . Intoduzione, testo greco, traduzione e note di commento, Acireale-Roma 2012, pp. 512. Paris 2012, pp. 164.